LAJU PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN BOTIA (Chromobotia macracanthus) DENGAN PAKAN CACING SUTERA (Tubifex sp.) Growth Performance and Survival Rate of Botia Larvae (Chromobotia macracanthus) with Feeding Tubifex Worms (Tubifex sp.) - Romi Pindonta Tarigan; Yunasfi Djayus; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Botia (Chromobotia macracanthus) is a freshwater fish that are having economic value is important because it has high sale value, especially in the ornamental fish market in North Sumatra. Life food is an important factor in the cultivation of ornamental fish. The research was conducted to determine the effect of feeding Tubifex worms (Tubifex sp.) on the growth performance and survival rate of Botia larvae. Tubifex worm culture do by using a wooden box with a recirculation system and the maintenance of Botia larvae done with volume 72 liter aquarium in a closed room.Experimental design using a completely randomized design with 5 treatments with 3 replications, as follows; 1) The Tubifex worms culture given chicken manure fermentation, 2) The Tubifex worms culture given cow manure fermentation, 3) The Tubifex worms culture given sheep dung fermentation, 4) Tubifex without treatment, 5) Pellet ornamental fish. The survival rate was 100 % in each treatments. Feeding the Tubifex worms are cultured with sheep dung fermentation gives the best results on the survival rate (SR), the absolute length (L), absolute weight (W), and daily growth rate (GR), respectively 1.02 cm, 0.91 g, and 2.57% for 30 days of maintenance.Keywords: Artificial feed, Botia, Tubifex.